Transformasi Digital Sistem Pembayaran UMKM melalui QRIS di Kawasan Wisata Makam Raja-Raja Imogiri Yogyakarta - Junga, Jihaan Nabiilah; Airawaty, Diana (Lembaga Pengembangan Kinerja Dosen, 2025)
The digital transformation of payment systems has become essential for micro, small, and medium enterprises (MSMEs) to improve transaction efficiency and expand market accessibility. This community service program was conducted to introduce and implement the use of QRIS through the Dana Bisnis application for four MSMEs located in the Makam Raja-Raja Imogiri tourism area Yogyakarta : Warung Wahyu, Warmindo Babe, Warung Pecel Bu Yani, and Warung Pecel Bu Elti. Initially, all MSMEs relied solely on cash transactions, leading to difficulties in financial recording and limited access to digital financial services. The program consisted of several stages, including on-site surveys, problem identification, explanation of digital payment benefits, training on QRIS registration and usage, and continuous assistance during the transition process. The results indicate a significant improvement in MSMEs’ understanding of digital payment systems and a gradual shift towards non-cash transactions. Evaluation findings show that approximately 60% of daily transactions were conducted via QRIS, and business owners reported benefits such as simplified bookkeeping, faster payment processing, and enhanced transaction security. This program demonstrates that QRIS-based digital payment systems can be effectively implemented in traditional MSMEs through proper mentoring and hands-on guidance. The initiative also plays a strategic role in promoting financial inclusion and strengthening MSME competitiveness in tourism areas. Continued efforts remain necessary, particularly in enhancing digital literacy and expanding access to supporting technology to ensure equitable adoption of digital payment systems.